2021
DOI: 10.1108/josm-12-2020-0448
|View full text |Cite
|
Sign up to set email alerts
|

Robotic involvement in the service encounter: a value-centric experience framework and empirical validation

Abstract: PurposeTaking a mixed-method approach, this research developed and validated a novel, value-centric experience framework delineating robotic involvement in the service encounter and its subsequent impact on customers' experiences.Design/methodology/approachFocused on robotic restaurant businesses where robots are mainly involved in food production processes, this research utilized online customer review data and a multistage, mixed-method design for empirical examination. Automated thematic analysis was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 74 publications
0
32
0
Order By: Relevance
“…In marketing, Hirschman and Holbrook (1982) introduced a more experiential view of consumption, including hedonic reasons to the more traditional utilitarian reasons for a purchase. Likewise, contemporary studies investigate the effect of utilitarian and hedonic value on repeat patronage (Hepola et al , 2020) or as dimensions of experiential value of robots in the service encounter (Wu et al , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In marketing, Hirschman and Holbrook (1982) introduced a more experiential view of consumption, including hedonic reasons to the more traditional utilitarian reasons for a purchase. Likewise, contemporary studies investigate the effect of utilitarian and hedonic value on repeat patronage (Hepola et al , 2020) or as dimensions of experiential value of robots in the service encounter (Wu et al , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Perceived role significance is the extent to which customers consider the role of service robots in a service encounter as significant, relevant and meaningful (Wu et al , 2021). To co-create value, both the customer and the service provider must engage in an active and high-quality interaction (Prahalad and Ramaswamy, 2004).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…As a result, they are more likely to trust the service robot and participate in the value co-creation process (Roy et al , 2020). Furthermore, guests may feel more relaxed and appreciate the service experience because competent service robots can save time and effort (Wu et al , 2021). For example, Belanche et al (2021) showed that customer perception of frontline robots’ competence positively influences functional, monetary and emotional value.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have compared consumer perceptions of robot and human services (Belanche et al , 2020; Byrd et al , 2021; Leung and Wen, 2020). In addition, some studies have investigated the antecedents of customer behavioral intention toward robot restaurants, including consumer innovativeness (Kim et al , 2021; Kwak et al , 2021), firm motivations (Belanche et al , 2021), the value, coolness and innovativeness perceptions of robot restaurants (Chuah et al , 2021; Cha, 2020; Hwang et al , 2020), the human-likeness attributes and service attributes of robots (Jang and Lee, 2020; Lu et al , 2021) and robot involvement characteristics (Wu et al , 2021).…”
Section: Research Background and Hypotheses Developmentmentioning
confidence: 99%